REVITALISASI KEBIJAKAN PEMBANGUNAN KEHUTANAN DI KALIMANTAN TIMUR PERIODE LIMA TAHUN KE-2 OTONOMI DAERAH (2006-2010) - Daroni, H. Rusdi Manaf (Pusjar SKPP Lembaga Administrasi Negara, 2006)
East Kalimantan’s natural resources have been the main sector in terms of financial contribution to the national income. Reforestration fund, provision of forest resources, export taxes, and other significant levies, have taken essential part in bearing the national development processes. This implies the positive roles of Kalimantan forest, for which it should be properly managed. Until recently, unfortunately, forest management has been observed to be unsuccsesful as indicated by depletion and degradation of forest areas during the first period of the implementation of regional autonomy (2001-2005). Under the new vision “forest management for the shake of resource sustainability and people’s wellbeing”, the following efforts are truthfully required: reassessment of performance measurement, revitalization through soft landing, reinforcing forest rehabilitation movement, reevaluation of policies concerning administrative approval (perijinan), etc. The ultimate goal of such endeavors is to achieve the optimum equilibrium of the forest function, i.e. between economic interest and ecological interest. Keywords: kinerja kehutanan, kapasitas kelembagaan, restrukturisasi dan revitalisasi, peranan ekologis dan sosial ekonomi hutan.